The Impact of Infectious Epidemic on Small and Medium Scale Enterprises in Nigeria a Case Study of Coronavirus Disease - Omolaja Tosin Samuel (Newinera Publisher, 2024)
This research work empirically explored the impact of infectious epidemic on small and medium scale business enterprises in Nigeria a case study of corona virus disease. The objectives of this study were to examine the level of coronavirus disease in Nigeria, investigate the impact of coronavirus disease on the survival of small and medium scale enterprises in Nigeria. The scope of the study is business owners in Nigeria; the infectious disease transmission mechanism theory was used as a framework. The research design used for this study is survey; the population targeted for this study consists of all business owners across the country. 115 business owners were used as sample size and cluster sampling technique was applied. Instrument used for this study is the questionnaire. Data collected were collected from primary sources. From the analysis of the data, the findings shows that the level of coronavirus disease in Nigeria as compared to other countries is average, coronavirus disease has effect on the survival of small and medium scale enterprises in Nigeria. Following the findings, it was recommended that measures should be devised to curb the spread of the virus and vaccines which have been created to prevent further hinge on the smooth operations of small and medium scale business activities should be administered appropriately, business owners should devise a means to continue their business by taking it online. The study concludes that coronavirus disease has a negative effect on small and medium scale business enterprises.